Peran Pemuda Desa Pulosari dalam Pemberdayaan Peternak Sapi Perah - Gaguk Heri Setiawan (CV Putra Publisher, 2023)
Youth Role is a form of effort made by youth to achieve the goals they have planned.aThis researchawas structured to findaout the role of the youth of Pulosari village in empowering dairy farmers, itais also hoped that it willabe able to provide a new understandingaof rational choice theory and sociological studies of empowerment and can beaused as a reference in analyzing studies related to the role of youth in empowering dairy farmers. The researchamethod used isia qualitative method. Qualitative methodaas a research procedure thataproduces descriptive data inathe form ofawritten or spoken wordsafrom observable people orabehavior. The research was directed at obtaining facts relatedato the role of youth in participating in helping dairy farmers in the Pulosari Village area, Bareng District, Jombang Regency to have an attitude of innovation in developing their livestock products. Thearole of youth is needed inathe era of modernization which cannot be stopped by humans. There are many roles that can be played by youth, from empowerment to developing innovations. But the action did not go smoothly. In accordanceawith the theoryaof rational choice that humans take an action whether intentional or unintentional, it is all a choice and must be carried out to achieve a goal. Young people make very risky choices but they are brave and responsible for the decisions they make because there are values ​​that are inaline with the goals and desires of the youth for the welfare of the breeders. As youth we must dare to take risks in making a decision for the realization of the goals they want.